2002
DOI: 10.1021/la020436n
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Behavior of Polyelectrolyte Complexes at the Solid/Liquid Interface

Abstract: Conformation of polymers at solid/liquid interface is an important property that determines their effectiveness in processes such as dispersion, deposition, adhesion, and wettability. In this work, conformational behavior of pyrene labeled poly(maleic acid-co-propylene), MS-P*, in solution and at the alumina surface and its changes upon perturbation in solution pH or addition of a second oppositely charged polymer than the ones in solution were studied using fluorescence spectroscopy. Conformation of this weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Fluorescence and total organic carbon measurements of the supernatant indicated absence of detectable free polymer in solution or desorption of preadsorbed polyanion or polycation. It is important to note that former studies have shown irreversibility of certain relaxation and reconformation processes of the polyanion in the polyelectrolyte complex or adsorbed on alumina [39]. Evidently, once the polyanion is anchored on the surface or bound in a polyelectrolyte complex, its behavior is dependent on the already altered conformation with possibly only partial reconformation to reach an energetic minimum.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Fluorescence and total organic carbon measurements of the supernatant indicated absence of detectable free polymer in solution or desorption of preadsorbed polyanion or polycation. It is important to note that former studies have shown irreversibility of certain relaxation and reconformation processes of the polyanion in the polyelectrolyte complex or adsorbed on alumina [39]. Evidently, once the polyanion is anchored on the surface or bound in a polyelectrolyte complex, its behavior is dependent on the already altered conformation with possibly only partial reconformation to reach an energetic minimum.…”
Section: Methodsmentioning
confidence: 97%
“…The result of the reaction is a covalently attached label to the polymer via a cyclic imide bond. The behavior of the labeled MS-P * in solution and adsorbed on the surface has been described in detail elsewhere [39]. Aminopyrene and amino-TEMPO were purchased from Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular conformations of sphere, sponge, sheets [7], globule [10], ring [8] and, cone [12] were observed. The NOM origin and solution properties, as two major factors, controlled the conformation of NOM [13,14]. Diverse structures with respect to NOM concentration [7,9], solution pH [10,11], ionic strength [9,10], and cation electrolyte identity [9] were also reported.…”
Section: Microtopography Of Nommentioning
confidence: 99%
“…At the same time, positive [9] or inverse [10] correlation between K oc and the molecular weight were reported depending on the origin and/or fractional composition of the aggregated humic materials. Besides the investigation on NOM structures, solution properties including pH value, ionic strength, and cationic electrolyte characteristics had been demonstrated to greatly alter the structure of NOM [4,12]. However, only few researches were focused on the impact of solution property on HOCs' partition to NOM.…”
Section: Introductionmentioning
confidence: 99%